If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + 9(-4) = -18 Multiply 9 * -4 -9x + -36 = -18 Reorder the terms: -36 + -9x = -18 Solving -36 + -9x = -18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + -9x = -18 + 36 Combine like terms: -36 + 36 = 0 0 + -9x = -18 + 36 -9x = -18 + 36 Combine like terms: -18 + 36 = 18 -9x = 18 Divide each side by '-9'. x = -2 Simplifying x = -2
| 12x-10=395 | | 4(n-8)=2 | | 770/55x?=42 | | (2/5)c-12=2 | | 17m+13-5=15m+8+2m | | 4-2=3 | | t-9=2t-3 | | 7x-8+13-5x=-7 | | (6x-13)=140 | | 180=2(4x+1)+5x-4 | | 2.1v=1.68 | | 16x=52.8 | | 3/2k=9/2 | | F(-X)=2(-x)-5 | | 3(n-8)=3n-24 | | 5(-2x-4)=20 | | x-42=-10 | | X-24=28+3x | | 175m-125m+43425=45000-175m | | -8x-9(-19)=11 | | 9/2/9-4/-1/2 | | 16/13p-9p | | -22x-6=39 | | 2x=360-120 | | -5-8+-5j-1-7= | | 4(5+6x)=20 | | 1/4*5/3 | | 2x+55=90 | | 3x+32=25 | | 10x-151=89+2x | | 3(I+1)=5(I-3) | | 2x=360-200 |